Mesoporous tin oxide: an efficient catalyst with versatile applications in acid and oxidation catalysis - Manjunathan, Pandian; Marakatti, Vijaykumar S.; Chandra, Prakash; Kulal, Atul B.; Umbarkar, Shubhangi B.; Ravishankar, Raman; Shanbhag, Ganapati V. (Catalysis Today, 2018)
Mesoporous tin oxide was prepared by template assisted and template-free methods. As-prepared materials were calcined at various temperatures to generate different nature (Bronsted and Lewis), amount and strength of acidic sites. The physico-chemical properties of the catalysts were studied by XRD, N-2 sorption, pyridine-FTIR, NH3-TPD, DRS UV-vis, TGA, SEM, TEM, H-1 MAS and Sn-119 MAS NMR analyses. The catalytic behavior of mesoporous tin oxide catalysts was evaluated for acetalization and ketalization of glycerol with benzaldehyde and acetone respectively under solvent free conditions. The catalytic performance of mesoporous tin oxide was compared with that of other conventional solid acid catalysts namely H-ZSM-5, H-mordenite, H-beta, Al-MCM-41, Al-SBA-15 and Al-TUD-1. The efficiency of mesoporous tin oxide was also tested for cyclohexene epoxidation reaction. The catalyst prepared by template assisted method showed excellent catalytic performance compared to other catalysts due the difference in nature and amount of acidic sites in the catalyst. Meso-SnO2-T-350 was stable and reusable catalyst for four cycles without any appreciable loss in activity, and therefore it offers a good catalyst for potentially wide applications.